Effenberg, A.O., Schmitz, G., Baumann, F., Rosenhahn, B., Kroeger, D. 2015. SoundScript – Supporting the Acquisition of Character Writing by Multisensory Integration. The Open Psychology Journal 8: 230-237. - Magalhães, Violeta Amélia (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2022)
.